2007
DOI: 10.1093/sleep/30.5.585
|View full text |Cite
|
Sign up to set email alerts
|

ERP Evidence of Enhanced Excitatory and Reduced Inhibitory Processes of Auditory Stimuli During Sleep in Patients With Primary Insomnia

Abstract: Patients with insomnia showed an enhancement in attention and a reduction in the inhibitory process that normally facilitates sleep onset in the beginning part of sleep. The results partially support the hyperarousal theory, ie, enhanced information processing during the initiation of sleep is a contributing factor for insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…This is similar to a previous study in adults with OSAS, in which the main AEP outcome was N550 (17). In the current study we documented the presence of a P900 as well, which has been reported to increase with the deepening of sleep, and has been associated with maintenance of sleep (33,34). Therefore, the presence of this peak in children with OSAS is consistent with one of the main differences between adult and pediatric OSAS: the conserved sleep architecture in children with OSAS (35).…”
Section: Aep During Sleepsupporting
confidence: 92%
“…This is similar to a previous study in adults with OSAS, in which the main AEP outcome was N550 (17). In the current study we documented the presence of a P900 as well, which has been reported to increase with the deepening of sleep, and has been associated with maintenance of sleep (33,34). Therefore, the presence of this peak in children with OSAS is consistent with one of the main differences between adult and pediatric OSAS: the conserved sleep architecture in children with OSAS (35).…”
Section: Aep During Sleepsupporting
confidence: 92%
“…The authors did not observe any between group differences, from evening to morning, when insomnia individuals were compared to GS. On the other hand, Yang and Lo (2007) observed a larger N1 and a smaller P2 in individuals with insomnia than in GS during the first 5 min of continuous stage 2 sleep, supporting the hyperarousal hypothesis. Recently, our research group recorded ERPs over multiple nights during wakefulness and sleep onset as an oddball paradigm was delivered to Psy-I and GS during the 3rd and 4th nights in the sleep laboratory (in the evening and upon awakening), with the addition of sleep-onset recordings on the 4th night.…”
Section: Introductionmentioning
confidence: 53%
“…If individuals with insomnia are unable to inhibit information processing, it would be expected that the changes from the waking ERPs to the sleeping one would be different from what is generally observed among GS. Although hyperarousal has already been investigated using the ERPs technique with insomnia individuals Devoto et al, 2005;Kertesz and Cote, 2011;Sforza and Haba-Rubio, 2006;Yang and Lo, 2007), the inability to inhibit information processing during sleep onset as well as during sleep itself remains to be clarified. The poor sleep experienced by insomnia individuals may be the result of an inability to inhibit external information processing of irrelevant stimulus during sleep onset and sleep and this enhanced information processing may result in hyperarousal.…”
Section: Introductionmentioning
confidence: 99%
“…First, Yang and Lo (2007) reported that insomniacs show larger N1 and smaller P2 to rare tones as well as smaller N350 to standard tones than controls during the first 5 min of continuous stage 2 sleep. However, observed that during the different stages of sleep, and contrary to what Yang and Lo (2007) had reported, insomniacs and good sleepers did not differ on measures of N1 and P2 during the night. Thus the issue of hyperarousal during the night, as measured with ERPs, requires more investigations as contradictory results are reported to this point.…”
Section: Event-related Potentials (Erps)mentioning
confidence: 99%